Mersilene tape versus conventional sutures in transvaginal cervical cerclage: a systematic review and meta-analysis - Juntao feng; Shisi Wei; Lihong Pang (BMC, 2023)
Abstract Objective This study aimed to assess the effectiveness of Mersilene tape versus alternative suture types in prolonging singleton pregnancies as well as other pregnancy and neonatal outcomes, in cases of history-, ultrasound-, and exam-indicated cervical cerclage. Methods A systematic review was conducted to identify relevant studies comparing different suture types in cervical cerclage procedures. The primary outcome of interest was preterm birth (PTB) rate < 37, <35, < 28, and < 24 weeks. Statistical analyses were performed to determine the relationship between suture type and various outcomes. Results A total of five studies, including three randomized controlled trials (RCTs) and two retrospective studies, with a combined participation of 2325 individuals, were included. The pooled analysis indicated no significant association between suture type and PTB at less than 37 weeks of gestation (RR: 1.02, 95% CI: 0.65-1.60, p < 0.01, I2 = 74%). Women who received Mersilene tape had a higher risk of PTB at 34-37 weeks (RR: 2.62, 95% CI: 1.57-4.37, p = 0.69, I2 = 0%), but a lower risk of PTB at less than 34 weeks (RR: 0.43, 95% CI: 0.28-0.66, p = 0.66, I2 = 46%). No statistically significant differences were observed for PTB before 28 weeks (RR: 1, 95% CI: 0.65-1.53, p = 0.70, I2 = 0%), before 24 weeks (RR: 0.86, 95% CI: 0.60-1.23, p = 0.33, I2 = 0%), incidence of chorioamnionitis (RR: 0.97, 95% CI: 020-4.83, p < 0.01, I2 = 95%), neonatal intensive care unit (NICU) admission (RR: 0.79, 95% CI: 0.28-2.22, p = 0.08, I2 = 67%) and neonatal death (RR: 1.00, 95% CI: 0.42-2.35, p = 0.17, I2 = 48%). Conclusion Our findings suggest that Mersilene tape does not reduce the risk of PTB before 37, 28 or 24 weeks. We observed higher risk of preterm birth between 34 and 37 weeks with Mersilene tape but lower incidence before 34 weeks, a period with higher neonatal morbidity and mortality. Due to the limited number of studies, our results and their clinical significance should be interpreted with caution.